Vaccination techniques in fish - Kürşat Kav; Osman Erganiş (Eurasian Journal of Veterinary Sciences)
In recent years, fish vaccines are heavily used in aquaculture against bacterial and viral infections. Injection and/or immersion type vaccines that are used commonly are prepared by inactivation of antigen with formaldehite. Vaccines are used effectively against bacterial (Vibrio spp. Aeromonas spp, Yersinia spp, pasteurella spp, Streptococcus spp.) and viral infections (Viral haemorrhagic septicaemia (VHS), Infectious Hematopoietic Necrosis (IHN), Infectious Pancreatic Necrosis (IPN), etc) in aquaculture and sea water. In this rewiev, vaccination techniques and mechanisms of immunization are described in aquaculture.